Mengurai Adaptasi Karir Lintas Batas: Studi Fenomenologi Entrepreneurial Mindset Lulusan Sains dan Sosial di Sektor Pendidikan dan Kuliner - Jeka Widiatmanta; Milatul Fadhilah; Retno Heny Saputri (CV. ALIM'SPUBLISHING, 2026)
The dynamics of the labor market in Indonesia currently demonstrate an increasingly complex pattern of career diversification. University graduates frequently undertake dual roles that are not aligned with their formal educational backgrounds. This phenomenon indicates that individuals no longer rely solely on their professional identities but increasingly require adaptive career strategies to maintain economic stability while simultaneously pursuing new opportunities. This study explores the process of cross-boundary career adaptation and the development of an entrepreneurial mindset among three administrative staff members at Universitas Islam Balitar with educational backgrounds in International Relations, Chemistry, and Mathematics. Employing an interpretive-hermeneutic phenomenological approach, data were collected through in-depth interviews, non-participant observation, and documentation, and subsequently analyzed using the modified Stevick-Colaizzi-Keen procedure (Moustakas, 1994). The research was conducted from January to June 2026. The analysis generated four major themes: (1) the transformation of formal academic skills into strategic capital within entrepreneurial activities; (2) dual orientations between bureaucratic stability and business opportunities; (3) identity negotiation and role synchronization; and (4) the entrepreneurial mindset as the primary driver of career adaptation. The phenomenological synthesis reveals that cross-boundary career adaptation represents a form of Coerced Career Construction, in which individuals integrate Savickas’ four dimensions of career adaptability with an entrepreneurial mindset to transform formal cognitive skills into strategic assets within informal agribusiness activities. This study contributes to Savickas’ theory by identifying non-linear cognitive skill transfer as a key mechanism of adaptation and by emphasizing the significance of the entrepreneurial mindset as a crucial psychosocial component within emerging economic contexts.